2019
DOI: 10.1073/pnas.1906623116
|View full text |Cite
|
Sign up to set email alerts
|

Alternative pathway androgen biosynthesis and human fetal female virilization

Abstract: Androgen biosynthesis in the human fetus proceeds through the adrenal sex steroid precursor dehydroepiandrosterone, which is converted to testosterone in the gonads, followed by further activation to 5α-dihydrotestosterone in genital skin, thereby facilitating male external genital differentiation. Congenital adrenal hyperplasia due to P450 oxidoreductase deficiency results in disrupted dehydroepiandrosterone biosynthesis, explaining undervirilization in affected boys. However, many affected girls are born vir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
67
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 42 publications
0
67
1
Order By: Relevance
“…The presence of unidentified rare mutations modulating the phenotype cannot be excluded; however, it is unlikely due to the frequent occurrence of SV form with P30L mutation in studies with meticulous genotyping. Some other factors modifying phenotype have also been suggested such as the CAG repeats of the androgen receptor and other genes encoding proteins other than cytochrome P450 type II enzyme with a 21-hydroxylase activity, as well as alternative pathway of androgen biosynthesis causing fetal virilization in females [ 58 60 ].…”
Section: Molecular Structure Of P30l Mutation and Functional Analysismentioning
confidence: 99%
“…The presence of unidentified rare mutations modulating the phenotype cannot be excluded; however, it is unlikely due to the frequent occurrence of SV form with P30L mutation in studies with meticulous genotyping. Some other factors modifying phenotype have also been suggested such as the CAG repeats of the androgen receptor and other genes encoding proteins other than cytochrome P450 type II enzyme with a 21-hydroxylase activity, as well as alternative pathway of androgen biosynthesis causing fetal virilization in females [ 58 60 ].…”
Section: Molecular Structure Of P30l Mutation and Functional Analysismentioning
confidence: 99%
“…Mutations in the electron donor enzyme POR invariably disrupt CYP17A1 and CYP21A2 activities ( 3 ), but have variable effects on CYP19A1 aromatase ( 4 ). We observed wild-type–equivalent CYP19A1 activity for the POR A287P mutant, within the linear range of the enzymatic reaction ( 2 ). When assessing full enzyme kinetics, Flück and coworkers ( 4 ) observed that POR A287P mildly impairs CYP19A1 activity, although catalytic efficiency was similar to wild-type POR.…”
mentioning
confidence: 71%
“…Newborn girls with P450 oxidoreductase (POR) deficiency regularly present with virilized external genitalia despite low circulating androgens ( 1 ). In PNAS, we ( 2 ) explain this conundrum by enhanced prenatal activity of an alternative androgen pathway ( Fig. 1 ) while classic androgen biosynthesis is disrupted.…”
mentioning
confidence: 95%
See 2 more Smart Citations